Hidroksi Metil Glutaril Coenzyme-A (HMG CoA) Reduktase Inhibitor and New Onset Diabetes Mellitus: A Review of Correlation and Clinical Implication - Wardani, Indah Sapta (Postgraduate, University of Mataram, 2023)
Treatment of lipid abnormalities with HMG CoA reductase inhibitor (statin) has been used for diabetic and non diabetic patients. Various studies have describe increased risk of new onset diabetes associated with statin therapy. This review aims to explain potential mechanism that related to diabetogenic effect of statin. This research was created by collecting literature that relevant to the topic. The types of literature used are clinical trials, meta analyzes and systematic reviews between 2013 until 2021. HMG CoA reductase is the target of statin therapy and the acting of this enzyme is inhibited by statin in competitive way. In vivo and in vitro studies reveal that statin reduce synthesis of mevalonate pathway and increase cholesterol transport that influence B cell function and decrease of insulin sensitivity and insulin secretion by multiple mechanism. Recent genetic study suggest that increased risk of type 2 diabetes mellitus pathway explained by gene variant target for LDL cholesterol lowering drugs. Accumulating evidence from several statin studies suggest that pravastatin is the least diabetogenic statin. Simvastatin, atorvastatin and rosurvastatin are more diabetogenic statin. The used of statin in clinical practice should concerned about benefit on cardiovascular while still considering the possible risk of developing type 2 diabetes mellitus. Regular monitoring of patients glycemic control is mandatory